Melatonin Can Modulate the Effect of Navitoclax (ABT-737) in HL-60 Cells - Alexey Lomovsky; Yulia Baburina; Irina Odinokova; Margarita Kobyakova; Yana Evstratova; Linda Sotnikova; Roman Krestinin; Olga Krestinina (MDPI AG, 2020)
Melatonin (N-acetyl-5-methoxytryptamine MEL) is an indolamine that has antioxidant, anti-inflammatory and anti-tumor properties. Moreover, MEL is capable of exhibiting both anti-apoptotic and pro-apoptotic effects. In the normal cells, MEL possesses antioxidant property and has an anti-apoptotic effect, while in the cancer cells it has pro-apoptotic action. We investigated the combined effect of MEL and navitoclax (ABT-737), which promotes cell death, on the activation of proliferation in acute promyelocytic leukemia on a cell model HL-60. The combined effect of these compounds leads to a reduction of the index of mitotic activity. The alterations in the level of anti- and pro-apoptotic proteins such as BclxL, Bclw, Mcl-1, and BAX, membrane potential, Ca2+ retention capacity, and ROS production under the combined action of MEL and ABT-737 were performed. We obtained that MEL in combination with ABT-737 decreased Ca2+ capacity, dropped membrane potential, increased ROS production, suppressed the expression of anti-apoptotic proteins such as BclxL, Bclw, and Mcl-1, and enhanced the expression of pro-apoptotic BAX. Since, MEL modulates autophagy and endoplasmic reticulum (ER) stress in cancer cells, the combined effect of MEL and ABT-737 on the expression of ER stress and autophagy markers was checked. The combined effect of MEL and ABT-737 (0.2 μM) increased the expression of protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK), leading to a decrease in the level of binding immunoglobulin protein (BIP) followed by an increase in the level of C/EBP homologous protein (CHOP). In this condition, the expression of ERO1 decreased, which could lead to a decrease in the level of protein disulfide isomerase (PDI). The obtained data suggested that melatonin has potential usefulness in the treatment of cancer, where it is able to modulate ER stress, autophagy and apoptosis.